2014
DOI: 10.1111/jgs.13063
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Embolism in Individuals Aged 80 and Older

Abstract: RESULTSTwo hundred twenty-four older adults with T2DM were included. Participant characteristics and a comparison of parameters between the four participant groups according to BMI at the time of the enrollment and at the end of follow-up are shown in Table 1. Statistical analysis of the relationship between BMI and eGFR after adjustment for age, sex, hypertension, eGFR, and albuminuria showed that a high BMI acted as a protective factor (BMI = 30 kg/m 2 , odds ratio = 0.36, 95% confidence interval = 0.04-0.68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Before the COVID-19 era, these data were confirmed, showing a four-to seven-fold increase in thrombotic complications in oncological patients compared with those in the general population [36]. Thus, the presence of oncological history was an independent mortality factor for elderly patients with PE events six months after hospital discharge [37]. Surprisingly, a traditional risk factor for PE as an oncological event has not been assessed in different COVID-19 patients [19,38].…”
Section: Discussion Key Findingsmentioning
confidence: 95%
“…Before the COVID-19 era, these data were confirmed, showing a four-to seven-fold increase in thrombotic complications in oncological patients compared with those in the general population [36]. Thus, the presence of oncological history was an independent mortality factor for elderly patients with PE events six months after hospital discharge [37]. Surprisingly, a traditional risk factor for PE as an oncological event has not been assessed in different COVID-19 patients [19,38].…”
Section: Discussion Key Findingsmentioning
confidence: 95%
“…In a previous study enrolled 24 patients with lung cancer and PE, Chuang et al showed that the most common symptoms were dyspnea (95.8%), hemoptysis (20.8%), cough (20.8%), chest pain (16.7%), body weight loss (8.3%), lower leg edema (8.3%), and shock (8.3%), which are not specific to lung cancer 25 [11]. Therefore, older patients with PE are less likely to present with chest pain and more likely to be hypoxic or have syncope 27,28 . In our study, 75.5% of older patients with PE presented with dyspnea, 9.4% with chest pain, and 3.8% with syncope, while 11.3% were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…. In another study enrolled28 cases with lung cancer having PE and 56 cases with lung cancer alone, Li et al found that 7.1% of patients with lung cancer complicated with PE were asymptomatic, and the incidence of cough (75.0% vs. 66.1%), stethalgia (25.0% vs. 7.1%), hemoptysis (14.3% vs. 19.6%), syncope (3.6% vs. 2.0%), palpitation (28.6% vs. 17.9%), and triad syndrome (3.6% vs. 0%) were similar between patients having lung cancer complicated with or without PE 26 . García Gómez LC conducted a hospital-based, case-control study included 413 patients with PE, 124 of whom were 80 years or older.…”
mentioning
confidence: 99%
“…The outcomes of patients admitted to our tertiary institution (Concord Hospital, University of Sydney, Australia) with confirmed PE had been reported previously (6,11,12). For the current study, consecutive patients admitted with a primary diagnosis of acute PE between January 2000 and December 2012 were identified from the PE database maintained by the Cardiology Department.…”
Section: Study Populationmentioning
confidence: 99%